Influence of simulated body condition score on growth, physiological responses and blood metabolites of native Malpura ram - MAURYA, V P; SEJIAN, V; NAQVI, S M K (The Indian Journal of Animal Sciences, 2012)
The effect of simulated body condition score (BCS) on body weight, wool yield, respiration rate, pulse rate and rectal temperature was evaluated in native Malpura ram. The rams were randomly divided into group 1 (2.5 BCS; n= 7), group 2 (BCS 3.0–3.5; n=7) and group 3 (BCS 4.0; n=7). Apart from grazing for 8 h a day, the rams were provided with concentrate mixture @ of 100 g, 300 g and 500 g to group 1, 2, and 3, respectively, to attain their respective BCS. The body weight (kg), heart girth (cm) physiological responses i.e. respiration rate (RR, breath/min), pulse rate (PR, beat/ min) and rectal temperature (RT °C) were recorded at fortnightly interval. The wool yield was recorded at 6 monthly interval clipping. The blood samples were also collected at fortnightly interval and analyzed for packed cell volume (PCV, %), hemoglobin (Hb, g/dl) and glucose (mg/dl). The animals of G1 had significantly lower (P<0.05) RR and RT than the other 2 groups of rams. A significant decrease in the body weight, HG and wool yield was observed in G1 rams as compared to G2 and G3 rams. The PCV, Hb and glucose values were significantly higher in G2, G3 animals than that of G1 animals.